Evaluation of socio-demographic variables affecting the periodontal health of pregnant women in Chandigarh, India - Jagjit Singh Dhaliwal; Gurvanit Lehl; Sachinjeet K Sodhi; Sonia Sachdeva (Journal of Indian Society of Periodontology, 2013)
Background: The literature is replete with reports that pregnant women have an increased level of periodontal disease as compared with non-pregnant women of the same age. There are many studies correlating the effect of periodontal disease on the adverse pregnancy outcomes. The development of periodontal diseases during pregnancy can be influenced by factors such as preexisting oral conditions, general health, and socio-cultural background. There is very little data studying the effect of socio-demographic factors on the periodontal health of pregnant women. This study evaluated the periodontal status of a sample of pregnant women of Chandigarh and adjoining areas. The study also investigated the relationship between these variables and a series of demographic and clinical variables. Materials and Methods: The participants were 190 pregnant women attending Gynecology and Obstetrics outpatient department of Government Medical College and Hospital, Chandigarh. The participants were examined for their periodontal health and various socio-demographic variables were recorded on performas designed for the purpose of study. Statistical analysis was done. Results: The results revealed that the mean bleeding index scores and probing depth increased with statistical significance when the socio-economic status was lower ( P<0.05). No significant differences were found in bleeding index scores and mean probing depth among different categories of profession, education, place of residence, and trimester of pregnancy ( P>0.1). The plaque index was not significantly associated with the socio-economic status, profession, place of residence, and trimester of pregnancy ( P>0.1). Conclusion: In the population of pregnant women investigated under this study, the clinical and socio-demographic characteristics showed non-significant correlation except socio-economic status which showed statistically significant correlation with bleeding on probing and pocket depth. Further studies may be required in Indian population to determine the association of periodontal diseases in pregnant women with socio-demographic variables.